2021
DOI: 10.3390/separations8090147
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Separation and Analysis of Five Compounds in Cibotium barometz by Micellar Electrokinetic Chromatography with Large-Volume Sample Stacking

Abstract: A large volume sample stacking (LVSS) method in micellar electrokinetic chromatography (MEKC) with diode array detector was developed for the simultaneous separation and analysis of five compounds: protocatechuic acid, protocatechuic aldehyde, caffeic acid, syringetin and vanillin in Cibotium barometz. The electrophoretic separation was performed in a 10 mM sodium dodecyl sulfate (SDS) and 50 mM sodium borax-sodium dihydrogen phosphate system (pH = 8.5) with 10% methanol at a separation voltage of 30 kV after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Recently, the most sensitive MEKC-UV with LVSS method was developed and validated for the simultaneous separation of five polyphenolic compounds (protocatechuic acid, protocatechuic aldehyde, caffeic acid, syringetin, and vanillin) in Cibotium barometz. The detection limits ranged from 32 to 65 pg, which were 12-27 times lower than those for MEKC and 500 times lower than previously reported (Wang et al, 2021).…”
Section: Mekc Analysis Of Various Tcmscontrasting
confidence: 53%
See 2 more Smart Citations
“…Recently, the most sensitive MEKC-UV with LVSS method was developed and validated for the simultaneous separation of five polyphenolic compounds (protocatechuic acid, protocatechuic aldehyde, caffeic acid, syringetin, and vanillin) in Cibotium barometz. The detection limits ranged from 32 to 65 pg, which were 12-27 times lower than those for MEKC and 500 times lower than previously reported (Wang et al, 2021).…”
Section: Mekc Analysis Of Various Tcmscontrasting
confidence: 53%
“…Furthermore, microwave-assisted extraction (MAE) (Li et al, 2017) and reflux (Gao et al, 2015) have been reported. The preconcentration methods include ITP (Chen et al, 2012), fieldamplified sample stacking (FASS) (Wang et al, 2018), field-amplified sample injection (FASI) (Duan et al, 2012), large volume sample stacking (LVSS) (Wang et al, 2021), and micelle to solvent stacking (MSS) (Yin et al, 2011). Some review papers for online sample preconcentration provide more extensive information on the theory and applications, such as FASS and t-ITP (Kitagawa and Otsuka, 2014;Kawai, 2017), sample stacking (Šlampová et al, 2018), and SPE (Dugheri et al, 2021) is recommended.…”
Section: Sample Preparation and Preconcentration Techniques Used For Tcmmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this drawback, LVSS combines with the polarity switching (PS) technique to remove a vacant sample matrix from the capillary to the inlet vial. By employing the PS-LVSS technique, Chinese medicine component [43], magnetic [44], and 3-hydroxyaspartate [45,46] were successfully concentrated and separated in CE. Nguyen et al reported an effective PS-LVSS method for fluorescent magnetic nanoparticles [44].…”
Section: Application Of Field-amplified Sample Stackingmentioning
confidence: 99%
“…The so‐called large‐volume sample stacking (LVSS), is a generally effective and well‐known on‐line preconcentration technique. In LVSS, the introduction of a large volume of sample solution prepared in a low‐conductivity matrix is allowed compared to normal injection [40]. Stacking occurs at the interface between the low‐conductivity sample zone and the running buffer zone.…”
Section: Introductionmentioning
confidence: 99%